Interfacial reinforcement of hybrid composite by electrophoretic deposition for vertically aligned carbon nanotubes on carbon fiber. (8th February 2020) - Li, Lizhi; Liu, Wenbo; Yang, Fan; Jiao, Weicheng; Hao, Lifeng; Wang, Rongguo
Abstract: In this paper, vertically aligned carbon nanotube/carbon fiber (VACNT/CF) hybrids was prepared by electrophoretic deposition (EPD) under mild conditions. The coaxial cylindrical electrode with CF filament as the cathode was employed to ensure dense VACNT arrays deposited on CF surface at low deposition voltage. The effect factors on the carbon nanoparticles alignment were investigated by the micro-morphology observations of hybrid fibers, including the diameter of carbon nanoparticles, types of solvent, deposition voltages, deposition time and the concentrations of carbon nanoparticles in dispersion. The results indicate that the optimum electrophoretic deposition conditions for vertically aligned hybrid fibers is the diameter of carbon nanoscale reinforcements of 110–170 mm, acetonitrile (ACN) as the dispersion medium, deposition voltage of 30 V, deposition time of 20 s and dispersion concentration of the carbon nanoparticles of 0.01 mg/mL. Single fiber tensile testing was performed and manifested that EPD in a coaxially cylindrical electric field was not destructive and could preserve the mechanical properties of CF filaments. Results of interphase properties tests demonstrated that the contact angle and the interfacial shear strength (IFSS) were significantly improved by 48.3% and 58.1% compared to that of as-recieved CF, respectively. The interfacial enhancement mechanism was also explored in details. Graphical abstract: Image 1